2001
DOI: 10.1046/j.1432-1327.2001.02231.x
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and properties of synthetic chlorophyll proteins

Abstract: A chemoselective method is described for coupling chlorophyll derivatives with an aldehyde group to synthetic peptides or proteins modified with an aminoxyacetyl group at the :-amino group of a lysine residue. Three templateassembled antiparallel four-helix bundles were synthesized for the ligation of one or two chlorophylls. This was achieved by coupling unprotected peptides to cysteine residues of a cyclic decapeptide by thioether formation. The amphiphilic helices were designed to form a hydrophobic pocket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 74 publications
(114 reference statements)
0
24
0
Order By: Relevance
“…It has been proposed that the transmembrane helix domains of the ␣-polypeptides show a low level of sequence conservation when different proteobacteria are compared; the one exception is His31. The major determinant for the specific Bchl-B850 geometry may be found predominantly in the residues outside the transmembrane region (3, 7,32,36,43). It has been found that insertion of four residues (TTWA) towards the carboxy terminus of the transmembrane helix of the ␣-apoprotein leads to the absence of LH2 complexes (3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the transmembrane helix domains of the ␣-polypeptides show a low level of sequence conservation when different proteobacteria are compared; the one exception is His31. The major determinant for the specific Bchl-B850 geometry may be found predominantly in the residues outside the transmembrane region (3, 7,32,36,43). It has been found that insertion of four residues (TTWA) towards the carboxy terminus of the transmembrane helix of the ␣-apoprotein leads to the absence of LH2 complexes (3).…”
Section: Discussionmentioning
confidence: 99%
“…Our strategy to study the binding of BChl to membrane-embedded helices and the assembly to stable TMH/BChl pockets is based on the use of model BChl proteins, modified in particular near the BChl-binding sites. In previous works, ligation of the central magnesium atom of coherent Argon laser (Innova 100), to histidines of synthetic de novo peptides has been achieved by a chemical modeling approach (28,29). This approach, however, depends on the reconstitution with pigments in a non-native system and relies on aqueous systems, either by use of detergents or by rendering the helices water-soluble.…”
mentioning
confidence: 99%
“…With the challenge of design making rapid progress, several groups have begun to look at the incorporation of functional cofactors in hopes of producing de novo catalytic proteins (8)(9)(10)(11)(12)(13)(14). Many enzymes require mono-and dinuclear metal ions (15), metal clusters (ferredoxin and nitrogenase) (16), heme (cytochromes and globins) (17), and organic cofactors (flavin-and quinone-based enzymes) (18).…”
mentioning
confidence: 99%